A Facile Procedure for One-Pot Stable Conjugation of Two Proglucagon Cysteine-Containing Peptide Analogs - He, Rongjun; Mowery, Stephanie A.; Chabenne, Joseph; Finan, Brian; Mayer, John P.; DiMarchi, Richard D. (Frontiers in Endocrinology, 2021)
An efficient, one pot site-specific conjugation of two cysteine-containing peptides was achieved by use of a maleimide/iodoacetyl bivalent linker. Following the initial ligation step, the linker was converted from an unstable thiosuccinimide to a stable thioether by mild aqueous hydrolysis. This method enables efficient, straightforward peptide conjugation for biochemical and medicinal applications.